Trajectory Tracking in Autonomous Driving Based on Improved hp Adaptive Pseudospectral Method - Yingjie Liu; Qianqian Wang (World Electric Vehicle Journal)
Intelligent driving technology can effectively improve transportation efficiency and vehicle safety and has become a development trend in automotive technology. As one of the core technologies of autonomous driving, path tracking control is directly related to the driving safety and comfort of vehicles and therefore has become a key research area of autonomous driving technology. In order to improve the reliability and control accuracy of path tracking algorithms, this paper proposed a path tracking control method based on the Gaussian pseudospectral method. Firstly, a vehicle motion model was constructed, and then an optimal trajectory solving method based on the hp adaptive pseudospectral method was proposed. The optimal trajectory control problem with differential constraints was transformed into an algebraic constrained nonlinear programming problem and solved using the sequential quadratic programming and compared with traditional control methods. The simulation results show that the tracking error of the lateral distance under the condition of <semantics>μ=0.8</semantics> is smaller than that of <semantics>μ=0.4</semantics>. At the same time, the tracking error of the lateral distance under the condition of u = 30 km/h is smaller than that of u = 90 km/h. The optimal path tracking control using the improved hp adaptive pseudospectral method has higher accuracy and better control effect compared to traditional control algorithms. Finally, virtual and real vehicle tests were conducted to verify the effectiveness and accuracy of the improved hp adaptive trajectory control algorithm.